The immune system. - Parham, Peter, 1950- (New York : Garland, 2005)
The Immune System, Second Edition has been designed for use in immunology courses for undergraduate, medical, dental, and pharmacy students. This class-tested and successful textbook synthesizes the established facts of immunology into a comprehensible, coherent, and up-to-date account of how the immune system works, rather than presenting immunology as a chronology of experiments and discoveries. Emphasizing the human immune system, the text has been designed to break down the barriers which often divide basic and clinical immunology. The reader-friendly text, section and chapter summaries, and full-color illustrations make the book accessible and easily understandable to students. The Immune System is adapted from Immunobiology by Janeway, Travers & Walport.
Keywords: Celbiologie